AB1239-HPR Fatigue at diagnosis of inflammatory joint diseases - a predictor of fatigue during the course of disease despite of low disease activity. (15th June 2017) - Jakobsen, SH; Emamifar, A; Hansen, IMJ
Abstract : Background: Fatigue is a common symptom in patients suffering from inflammatory rheumatic diseases. Several patients still present with fatigue, although they are well treated with anti TNF-therapy (1). Objectives: To investigate disease-related aspects of fatigue in patients with inflammatory rheumatic diseases using the Functional Assessment of Chronic Illness Therapy-Fatigue (FACIT-F) with the aim later to develop methods to improve the patients quality of life in a more specific way. Methods: All patients with inflammatory diseases including Rheumatoid Arthritis (38) and Spondyloarthropathy (13) and Psoriatic arthritis (2) treated with Intravenous biologic from 15.10 until 31.12.16 were invited to fill out the FACIT-F questionnaire during intravenous (IV) infusion of the drugs in the rheumatology outpatient clinic. Furthermore hemoglobin and disease activity score were extracted from patients electronic records. Results: Of 72 patients, 53 patients completed the questionnaire. 5 patients did not want to participate. In 11 patients treatment was discontinued during the study and 3 patients were not able to answer the questions. Patients with a fatigue score of <30 had few problems with any of the subgroups within the FACIT-F questionnaire (A-E), whereas more than 30% of patients with a fatigue score of ≥30 had challenges in one of the FACIT-F subgroups (somewhat, quite a bit and very much) A. Physical well-being: lack of energy and troubles with meeting the needs of their family because of their physical condition. B. Social/family well-being: patients were not feeling close to their friends, not getting enough emotional support from their family and not satisfied with their sex life. C. Emotional well-being: patients worry if their conditions might get worse. D. Functional well-being: patients feel they are partly unable to work, not satisfied with their performance at work and they have sleeping and quality of life problems. E. Additional concerns: patients had problems with fatigue, weakness, tiredness, starting and finishing things because of tiredness, not having energy, not being able to do usual activities, frustration by being too tired to do the things they want to do as well as they want to limit social activities because of tiredness and they need to sleep during the day. Furthermore, there was a moderate correlation between fatigue at diagnosis and fatigue at time of data extraction (r =0.53). The fatigue was not correlated with anemia or high disease activity. Conclusions: Our results demonstrated that patients with a fatigue score of >30 had different challenges mentioned in the fatigue questionnaire. In addition, patients who experience fatigue at time of diagnosis, they often remain fatigue, provoking the thought that fatigue is not correlated with inflammatory joint disease. Maybe more explorative questions about fatigue at the consultation could be a part of improving the patients'quality of life. References: Druce KL, et al. Most patients who reach disease remission following anti-TNF therapy continue to report fatigue: results from the British Society for Rheumatology Biologics Register for Rheumatoid Arthritis. Rheumatology (Oxford). 2016;55:1786–1790. Webster K, Cella D, Yost K. The Functional Assessment of Chronic Illness Therapy (FACIT) Measurement System: properties, applications, and interpretation. Health Qual Life Outcomes 2003;1:79. Disclosure of Interest: None declared